PRACTICAL FORMULA OF EDUCATIONAL STANDARDS IN THE TRAINING OF QUALIFIED PERSONNEL - Tashkoziyeva , Zulfiya Eraliyevna (Educational Research in Universal Sciences, 2023)
A practical formula has been developed for the practical application of educational standards in the training of higher education students as professional personnel and ensuring employment. The development of practical work sequences aimed at acquiring theoretical and practical knowledge of the subjects of specialization (Engineering and computer graphics) is presented.